Dental ceramic restoration and surface modification material thereof

By using surface modification materials of polymerizable monomer compositions, volatile diluents and photopolymerization initiators, and using photopolymerization technology to form a dense coating, the problem of dimensional error of dental ceramic restoration is solved, crown size adjustment and surface modification are achieved, cost reduction and efficiency improvement.

CN119587384APending Publication Date: 2025-03-11JIAXING JINGYIN BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411814816.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing dental ceramic restorations are prone to dimensional errors during sintering, resulting in too large gaps between the crown and the teeth, causing food tamponade and inflammatory reactions, and existing modification materials cannot effectively solve this problem.

Method used

A surface modification material is used, which consists of a polymeric monomer composition, a volatile diluent and a photopolymerization initiator, to form a dense coating by photopolymerization technology to adjust the size and surface characteristics of the dental ceramic restoration.

Benefits of technology

This material can easily and directly modify the surface of dental ceramic restoration, effectively adjust the size of the crown, reduce the repair cost, improve the restoration efficiency, and meet the needs of surface modification and adjustment of dental ceramic restoration, especially the crown.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005181471820000111
    Figure BDA0005181471820000111
  • Figure BDA0005181471820000131
    Figure BDA0005181471820000131
  • Figure BDA0005181471820000151
    Figure BDA0005181471820000151
Patent Text Reader

Abstract

The invention relates to a dental ceramic restoration and a surface modification material thereof, the dental ceramic restoration is coated with the surface modification material to form a coating for size modification, the surface modification material comprises: a polymerizable monomer composition comprising 20-50 parts by weight of a first component and 0.2-5 parts by weight of a second component, the first component is a multi-polymeric-functional-group polymeric monomer containing three or more polymeric functional groups in a molecule, the density of the polymeric functional groups is greater than 8 mmol / ml, and the polymeric functional groups are in a solid state at room temperature or have the viscosity greater than 3000 cps at 25 DEG C; the second component is selected from a polymerizable monomer containing an acidic group or containing an acidic group and containing alkoxy silane; the volatile diluent is an organic solvent or a polymerizable monomer of which the vapor pressure is greater than or equal to 1Kpa and less than 10Kpa at room temperature; and a photopolymerization initiator, wherein the wavelength at the time of photopolymerization is 365 nm to 520 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to dental materials, in particular to a dental ceramic restoration and a surface modification material which can simply and directly modify the surface of the ceramic restoration. Background Art

[0002] With the increasing awareness of the metal allergy caused by metal restorations in the oral cavity and the development of dental ceramic technology, metal dental restorations (crowns, etc.) have been gradually replaced by high-strength dental ceramics such as zirconium dioxide, aluminum oxide, and lithium diselenate restorations. The production of dental ceramic restorations generally requires a sintering step. Although the shrinkage of the ceramic sintering process is considered in advance during the production process, due to the material itself and the influence of sintering conditions, the size of the restoration after sintering is often less than the expected size by tens to hundreds of microns. If these small-sized restorations, especially crowns, are installed in the patient's mouth, due to the large gap between the crown of the restoration and the crown tip of the adjacent tooth, it is very easy to cause food filling during chewing, poor postoperative experience, and easy to cause inflammatory reactions such as interdental papillitis and gingivitis, which further leads to alveolar bone absorption and increased interdental space, which is more likely to cause serious food impaction, forming a vicious cycle until the tooth is extracted.

[0003] The clinical approach to dealing with size errors in ceramic restorations is to try them out before installing them in the patient's mouth to confirm whether the gap between the restoration and the adjacent teeth is appropriate. If the gap is too large, the common response is to return the restoration to the restoration manufacturing factory for surface modification, that is, to apply a ceramic layer with a certain adhesion to the crown surface and the required thickness on the existing crown to adjust the size of the crown. This modification method is time-consuming and labor-intensive, which not only increases the production cost, but also wastes the time of both doctors and patients.

[0004] In existing dental restoration treatments, when bonding with high-strength dental ceramics such as zirconium dioxide, aluminum oxide, and lithium diselenate restorations, ceramic pretreatment agents (or multifunctional adhesives) + resin cements are generally used for bonding operations. That is, the surface of the ceramic restoration is pretreated with a ceramic pretreatment agent containing an acidic monomer or a silane monomer or a multifunctional adhesive (containing an acidic monomer, containing a silane monomer, and other monomers), and then resin cement is used for bonding. On the one hand, these ceramic pretreatment agents or multifunctional adhesives contain a large amount of water and solvents. When pretreating the surface of the ceramic restoration, compressed air must be used to blow away the water and solvents, and only a small amount of acidic monomers, silane monomers, or a small amount of acidic monomers, silane monomers, and other monomers remain. These monomers remaining on the surface of the ceramic restoration, even if polymerized in the presence of a polymerization initiator, have an obvious oxygen-inhibited unpolymerized layer, and cannot form a dense, bright polymerized layer similar to ceramics. On the other hand, resin cement is a viscous paste composed of polymerizable monomers and fillers. It can neither form a uniform coating by coating nor form a dense, bright polymer layer similar to ceramics after polymerization. Therefore, the ceramic pretreatment agents or multifunctional adhesives and resin cement currently used in dental restoration treatment cannot meet the needs of surface modification and size adjustment of ceramic restorations, especially crowns. Therefore, the art urgently needs a material and method that can simply modify and adjust the surface of dental ceramic restorations, especially ceramic crowns. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a dental ceramic restoration and a surface modification material thereof in view of the above-mentioned defects of the prior art.

[0006] In order to achieve the above object, the present invention provides a surface modification material for modifying the surface of a dental ceramic restoration, which comprises:

[0007] A polymerizable monomer composition, comprising 20 to 50 parts by weight of a first component and 0.2 to 5 parts by weight of a second component, wherein the first component is a multi-functional polymerizable monomer having three or more polymerizable functional groups in the molecule, a polymerizable functional group density of the molecule greater than 8 mmol / ml, and being solid at room temperature or having a viscosity greater than 3000 cps at 25°C; and the second component is a polymerizable monomer selected from a group containing an acidic group or containing an acidic group and containing an alkoxysilane;

[0008] Volatile diluents are organic solvents or polymerizable monomers having a vapor pressure greater than or equal to 1KPa and less than 10KPa at room temperature; and

[0009] Photopolymerization initiator, the wavelength of photopolymerization is 365nm to 520nm;

[0010] Wherein, the polymerizable functional group density of the monomers of the polymerizable monomer composition is:

[0011] Monomer polymerization functional group density = N × D × 1000 / M;

[0012] Wherein, the unit of monomer polymerizable functional group density is mmol / ml, N is the number of polymerizable functional groups in one molecule of monomer; D is the density of the polymerizable monomer, in g / ml; M is the molar mass of the polymerizable monomer, in g / mol.

[0013] In the above-mentioned surface modification material, the first component is tris(2-acryloxyethyl)isocyanurate, polydipentaerythritol pentaacrylate or polydipentaerythritol hexaacrylate.

[0014] In the above-mentioned surface modification material, the acidic group of the second component is a carboxyl group, a carboxylic anhydride group and / or a phosphoric acid group.

[0015] In the above-mentioned surface modification material, the polymerizable monomer of the second component is 4-methacryloyloxyethyl trimellitic acid, 10-methacryloyloxydecyl phosphate, di-10-methacryloyloxydecyl phosphate, 11-acryloyloxyundecyl phosphoric acid and / or di-11-acryloyloxyundecyl phosphoric acid.

[0016] In the above-mentioned surface modification material, the organic solvent of the volatile diluent is ethanol or propyl acetate.

[0017] In the above-mentioned surface modification material, the polymerizable monomer of the volatile diluent is methyl methacrylate or ethyl methacrylate.

[0018] The above-mentioned surface modification material, wherein the photopolymerization initiator is an α-diketone compound, an alkyl phenone compound, an acyl phosphine oxide compound, a diocene titanocene compound, an oxime ester compound, a benzoin compound, an acetophenone compound, a benzophenone compound, a thioxanthone compound, an α-acyl oxime ester compound, a benzoylformate compound, a benzyl compound, an azo compound, a diphenyl sulfide compound, an organic pigment compound, an iron-phthalocyanine compound, a benzoin ether compound or an anthraquinone compound.

[0019] The surface modification material mentioned above further includes a polymerization accelerator, which is an amine compound, a sulfinic acid compound, a barbituric acid compound, an aldehyde compound or a thiol compound, and the polymerization accelerator is 0.5 to 3 times the weight of the photopolymerization initiator.

[0020] The above-mentioned surface modification material, among others, also includes a polymerization inhibitor, which is at least one of phenols such as hydroquinone, dibutylhydroquinone, hydroquinone monomethyl ether, 2,6-di-tert-butylphenol, 2,6-di-tert-butyl-p-cresol, catechol, pyrogallol, benzoquinone, 2-hydroxybenzoquinone, p-methoxyphenol, tert-butylcatechol, butylated hydroxyanisole, butylated hydroxytoluene, and tert-butylhydroquinone, and the added amount of the polymerization inhibitor is 50 to 20,000 ppm relative to the polymerizable monomer composition.

[0021] In order to better achieve the above-mentioned purpose, the present invention also provides a dental ceramic restoration, wherein the above-mentioned surface modification material is applied to form a coating for surface modification and size adjustment.

[0022] The technical effects of the present invention are:

[0023] The surface modification material of the present invention can simply and directly modify the surface of a dental ceramic restoration, and can modify and adjust the size of the dental ceramic restoration, especially the surface of a ceramic crown. It is easy to use and simple to operate, reduces the restoration cost, improves the restoration efficiency, and meets the needs of surface modification and size adjustment of dental ceramic restorations, especially crowns. DETAILED DESCRIPTION

[0024] The structural principle and working principle of the present invention are described in detail below:

[0025] The dental ceramic restoration of the present invention is coated with the following surface modification materials to form a coating for surface modification and size adjustment. The surface modification material is used for surface modification and size adjustment of the dental ceramic restoration, comprising: a polymerizable monomer composition, comprising 20 to 50 parts by weight of a first component and 0.2 to 5 parts by weight of a second component, wherein the first component is a multi-functional polymerizable monomer containing three or more polymerizable functional groups in the molecule, the polymerizable functional group density of the molecule is greater than 8 mmol / ml, and is solid at room temperature or has a viscosity greater than 3000 cps at 25°C; the second component is a polymerizable monomer selected from a polymerizable monomer containing an acidic group or containing an acidic group and containing an alkoxysilane; a volatile diluent is an organic solvent or a polymerizable monomer having a vapor pressure greater than or equal to 1KPa and less than 10KPa at room temperature; and a photopolymerization initiator, the wavelength of which during photopolymerization is 365nm to 520nm; wherein the polymerizable functional group density of the monomers of the polymerizable monomer composition is:

[0026] Monomer polymerization functional group density = N × D × 1000 / M;

[0027] Wherein, the unit of monomer polymerizable functional group density is mmol / ml, N is the number of polymerizable functional groups in one molecule of monomer; D is the density of the polymerizable monomer, in g / ml; M is the molar mass of the polymerizable monomer, in g / mol.

[0028] Wherein, the first component is tris(2-acryloyloxyethyl)isocyanurate, polydipentaerythritol pentaacrylate or polydipentaerythritol hexaacrylate. The acidic group of the second component is carboxyl, carboxylic anhydride or phosphoric acid; the polymerizable monomer of the second component is 4-methacryloyloxyethyl trimellitic acid, 10-methacryloyloxydecyl phosphate, di-10-methacryloyloxydecyl phosphate, 11-acryloyloxyundecyl phosphate and / or di-11-acryloyloxyundecyl phosphate. The organic solvent of the volatile diluent is ethanol or propyl acetate; the polymerizable monomer of the volatile diluent is methyl methacrylate or ethyl methacrylate. The photopolymerization initiator is an α-diketone compound, an alkyl phenone compound, an acyl phosphine oxide compound, a titanocene compound, an oxime ester compound, a benzoin compound, an acetophenone compound, a benzophenone compound, a thioxanthone compound, an α-acyl oxime ester compound, a benzoylformate compound, a benzil compound, an azo compound, a diphenyl sulfide compound, an organic pigment compound, an iron-phthalocyanine compound, a benzoin ether compound or an anthraquinone compound.

[0029] In this embodiment, a polymerization accelerator may be further included, and the polymerization accelerator is an amine compound, a sulfinic acid compound, a barbituric acid compound, an aldehyde compound or a thiol compound, and the polymerization accelerator is 0.5 to 3 times the weight of the photopolymerization initiator. A polymerization inhibitor may also be included, and the polymerization inhibitor is at least one of hydroquinone, dibutylhydroquinone, hydroquinone monomethyl ether, 2,6-di-tert-butylphenol, 2,6-di-tert-butyl-p-cresol and other phenols, catechol, pyrogallol, benzoquinone, 2-hydroxybenzoquinone, p-methoxyphenol, tert-butylcatechol, butylated hydroxyanisole, butylated hydroxytoluene, and tert-butylhydroquinone, and the addition amount of the polymerization inhibitor is 50 to 20000 ppm relative to the polymerizable monomer composition.

[0030] In this embodiment, the first component a1 of the polymerizable monomer composition A is a multi-functional polymerizable monomer having three or more (including three) polymerizable functional groups in the molecule, a polymerizable functional group density of the molecule of more than 8 mmol / ml, and a solid state at room temperature or a viscosity of more than 3000 cps at 25 degrees. The polymerizable functional group density of the monomer can be calculated as follows:

[0031] Monomer polymerizable functional group concentration (mmol / ml) = N × D × 1000 / M;

[0032] Wherein, N represents the number of polymerizable functional groups in one molecule of monomer; D represents the density of the polymerizable monomer (unit: g / ml), and M represents the molar mass of the polymerizable monomer (g / mol).

[0033] The density of the polymerizable functional groups of the first component a1 monomer is particularly important for the performance of the modified composition. When the density of the polymerizable functional groups of the monomer is lower than 8 mmol / ml, the cross-linking density of the polymerization is insufficient during photopolymerization, so that a dense, bright polymer layer similar to ceramic cannot be obtained. It is particularly important for the performance of the modified composition to be solid at room temperature or have a viscosity of more than 3000 cps at 25 degrees. When the monomer viscosity is lower than 3000 cps, the monomer coating left after the volatile diluent evaporates cannot effectively prevent air from entering the coating, which easily leads to the generation of an oxygen-inhibited unpolymerized layer during photopolymerization, so that a dense, bright polymer layer similar to ceramic cannot be obtained. The first component a1 has three or more (including three) polymerizable functional groups in the molecule, the concentration of polymerizable functional groups is above 8 mmol / ml, and the amount of the multi-functional polymerizable monomer is solid at room temperature or has a viscosity of 3000 cps or more at 25 degrees, relative to 100 parts by weight of the polymerizable monomer composition A, the volatile diluent B, and the polymerization initiator C. It is preferably 20 to 50 parts by weight, more preferably 25-45 parts by weight, and particularly preferably 30-40 parts by weight. When the amount is less than 20 parts by weight, the composition is easily coated on the ceramic surface and the coating is incomplete, and the desired coating thickness and size modification effect cannot be achieved. When the amount is higher than 50 parts by weight, the viscosity of the composition increases, which is easy to cause uneven coating during coating, thereby affecting the correct size modification.

[0034] The second component a2 is a polymerizable monomer containing an acidic group or a polymerizable monomer containing an acidic group and a polymerizable monomer containing an alkoxysilane. The polymerizable monomer containing an acidic group is a polymerizable monomer containing a phosphoric acid group, a carboxyl group and a carboxylic anhydride group, and these monomers can be used alone or in combination. When used, the polymerizable monomer containing a phosphoric acid group, a carboxyl group and a carboxylic anhydride group can form hydrogen bonds, ionic bonds, etc. with the ceramic surface, such as the metal oxide hydration layer on the surface of zirconium dioxide or aluminum oxide, through the acidic group, and the polymerizable functional group at the other end of the monomer can copolymerize with the monomer in the composition, thereby forming a coating with adhesion to the ceramic surface. The polymerizable monomer containing a phosphoric acid group, a carboxyl group and a carboxylic anhydride group has the ability to hydrolyze the alkoxysilane end of the polymerizable monomer containing an alkoxysilane to form a hydroxyl silicon group, thereby coupling reaction with the hydroxyl silicon group on the ceramic surface such as lithium diselenate, and the polymerizable functional group at the other end of the polymerizable monomer containing an alkoxysilane can copolymerize with the monomer in the composition, thereby forming a coating with adhesion to the ceramic surface.

[0035] The polymerizable monomer containing a phosphoric acid group, a carboxyl group and a carboxylic acid anhydride group can be selected from one or more of the following monomers: (meth)acrylic acid and its anhydride, 1,4-di(meth)acryloyloxyethyl pyromellitic acid, 6-(meth)acryloyloxyethylnaphthalene 1,2,6-tricarboxylic acid, N-(meth)acryloyl p-aminobenzoic acid, N-(meth)acryloyl o-aminobenzoic acid, N-(meth)acryloyl m-aminobenzoic acid, N-(meth)acryloyl-5-aminosalicylic acid, N-(meth)acryloyl-4-aminosalicylic acid, 4-(meth)acryloyloxyethyl trimellitic acid and its anhydride, 4-(meth)acryloyloxybutyl trimellitic acid and its anhydride, 4-(meth)acryloyloxyhexyl trimellitic acid and its anhydride, 4-(meth)acryloyloxydecyl trimellitic acid and its anhydride Monomers having a carboxylic acid group or anhydride group thereof, such as 2-(meth)acryloyloxybenzoic acid, 3-(meth)acryloyloxybenzoic acid, 4-(meth)acryloyloxybenzoic acid, β-(meth)acryloyloxyethyl succinate, β-(meth)acryloyloxyethyl maleate, β-(meth)acryloyloxyethyl phthalate, 11-(meth)acryloyloxy-1,1-undecanedicarboxylic acid, and p-vinylbenzoic acid; and monomers having a phosphate group, such as (2-(meth)acryloyloxyethyl)phosphoric acid, (2-(meth)acryloyloxyethylphenyl)phosphoric acid, 10-(meth)acryloyloxydecylphosphoric acid, 10-methacryloyloxydecyl phosphate, 11-(meth)acryloyloxyundecylphosphoric acid, and 11-methacryloyloxyundecyl phosphate. Preferred are one or more of the following monomers: 10-methacryloyloxydecyl phosphate, 11-(meth)acryloyloxyundecyl phosphate, di-11-methacryloyloxyundecyl phosphate, 4-methacryloyloxyethyl trimellitic acid and anhydrides thereof.

[0036] The amount of the polymerizable monomer containing a phosphoric acid group, a carboxyl group and a carboxylic anhydride group in the second component a2 of this embodiment is preferably 0.2 to 5 parts by weight, more preferably 0.3-4 parts by weight, and particularly preferably 0.5-3 parts by weight, relative to 100 parts by weight of the polymerizable monomer composition A, the volatile diluent B and the polymerization initiator C. When the amount is less than 0.2 parts by weight, the adhesion between the coating formed by the composition and the ceramic surface is low. When the amount is more than 5 parts by weight, the coating formed by the composition contains too many monomers with low polymerization functional group density, which affects the light cross-linking curing speed during light curing, and is prone to produce an oxygen-inhibited unpolymerized layer, which affects the density of the coating after light curing, so that a dense bright polymerized layer similar to ceramics cannot be obtained.

[0037] The polymerizable monomer containing alkoxysilane of the second component a2 of this embodiment can be hydrolyzed to form a hydroxyl silicon group when the polymerizable monomer containing phosphoric acid group, carboxyl group and carboxylic anhydride group coexists, thereby coupling reaction occurs with the hydroxyl silicon group on the surface of ceramics such as lithium diselenate, and the polymerizable functional group at the other end of the monomer can copolymerize with the monomer in the composition, thereby forming a coating having adhesion to the ceramic surface. The polymerizable monomer containing alkoxysilane of the second component a2 is preferably γ-methacryloxypropyl trimethoxysilane, γ-acryloxypropyl trimethoxysilane, γ-methacryloxypropyl triethoxysilane or γ-acryloxypropyl triethoxysilane. The amount of the polymerizable monomer containing alkoxysilane is preferably 0.5-3 times the weight of the monomer containing acidic group, more preferably 0.8-2.5 times the weight of the monomer containing acidic group, and particularly preferably 1-2 times the weight of the monomer containing acidic group.

[0038] The volatile diluent B of this embodiment is a polymerizable monomer or organic solvent with a vapor pressure of more than 1Kpa and less than 10Kpa at room temperature. The vapor pressure of the volatile diluent B at room temperature has a greater impact on the surface modification material. When the vapor pressure is low, there is too much residual diluent in the coating, and oxygen is easily generated during light curing to inhibit the unpolymerized layer, which affects the light cross-linking curing speed and the density of the coating after light polymerization, so that a dense bright polymerized layer similar to ceramics cannot be obtained. When the vapor pressure is high, the diluent evaporates rapidly during coating application, which easily leads to uneven coating. The polymerizable monomer or organic solvent with a vapor pressure of more than 1Kpa and less than 10Kpa at room temperature can be methyl methacrylate, ethyl methacrylate, methyl acrylate, ethyl acrylate, ethanol, n-butanol, ethyl acetate, propyl acetate or butyl acetate, preferably methyl methacrylate, ethyl methacrylate, ethanol, ethyl acetate or propyl acetate, more preferably methyl methacrylate, ethanol or ethyl acetate.

[0039] The photopolymerization initiator C of this embodiment can be any photopolymerization initiator that generates free radicals by irradiating light, and there is no particular limitation on this. As the wavelength used in photopolymerization, it can generally be 365nm to 520nm, preferably 370nm to 520nm in practice, and more preferably 380nm to 500nm. The photopolymerization initiator that generates free radicals at the wavelength of light used in photopolymerization can be an α-diketone compound, an alkyl phenone compound, an acylphosphine oxide compound, a titanocene compound, an oxime ester compound, a benzoin compound, an acetophenone compound, a benzophenone compound, a thioxanthone compound, an α-acyloxime ester compound, a benzoyl formate compound, a benzyl compound, an azo compound, a diphenyl sulfide compound, an organic pigment compound, an iron-phthalocyanine compound, a benzoin ether compound or an anthraquinone compound. Among them, an alkyl phenone compound or an acylphosphine oxide compound is preferred. The α-diketone compound may be α-cyclohexanedione, d,l-camphorquinone, camphorquinone-10-carboxylic acid or camphorquinone-10-carboxylic acid; the alkylphenone compound may be 1-hydroxy-cyclohexyl-phenyl-ketone (Omnirad 184: manufactured by IGM Resins BV); the acylphosphine oxide compound may be bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (Omnirad 819: manufactured by IGM Resins BV) or 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide (Omnirad TPO: manufactured by IGM Resins BV). The photocurable composition may contain only one photopolymerization initiator or two or more.

[0040] In this embodiment, the photopolymerization initiator can be used in combination with a polymerization accelerator as needed, and the polymerization accelerator can be an amine compound, a sulfinic acid compound, a barbituric acid compound, an aldehyde compound or a thiol compound. Among them, the amine compound is p-tolyldimethylamine, p-tolyldiethylamine, p-tolyldiethanolamine, ethyl p-dimethylaminobenzoate, alkyl esters such as isooctyl p-dimethylaminobenzoate, alkyl esters such as p-diethylaminobenzoic acid and methyl p-diethylaminobenzoate, N,N-dimethylaminoethyl methyl methacrylate, etc. The amount of the photoinitiator accelerator used is usually 0.5 to 3 times the weight of the amount of the photopolymerization initiator used.

[0041] The content of the photopolymerization initiator in this embodiment (the total content when two or more types and a polymerization accelerator are used) is preferably 0.5 to 5 parts by weight, more preferably 0.8 to 4.5 parts by weight, and particularly preferably 1 to 4 parts by weight, relative to 100 parts by weight of the total of the polymerizable monomer composition A, the volatile diluent B and the photopolymerization initiator C.

[0042] In the present embodiment, an inhibitor D may also be included, such as hydroquinone, dibutyl hydroquinone and other hydroquinone compounds, hydroquinone monomethyl ether, 2,6-di-tert-butylphenol, 2,6-di-tert-butyl-p-cresol and other phenols, catechol, pyrogallol, benzoquinone, 2-hydroxybenzoquinone, p-methoxyphenol, tert-butylcatechol, butylated hydroxyanisole, butylated hydroxytoluene, tert-butylhydroquinone, etc. The inhibitor can be used alone or in combination of two or more. Among them, a mixture of hydroquinone monomethyl ether and 2,6-di-tert-butyl-p-cresol is preferred. Relative to the polymerizable monomer (A), the addition amount of the inhibitor is 50 to 20000 ppm, more preferably 100 to 15000 ppm, and particularly preferably 200 to 10000 ppm.

[0043] The composition of the surface modification material of the present invention generally does not contain water, but a small amount of water can be appropriately added as needed. There is no particular restriction on the addition of water, and purified water or distilled water is preferred. The amount of water added is preferably 0.1 to 5 parts by weight, more preferably 0.2 to 4 parts by weight, and particularly preferably 0.5 to 3 parts by weight relative to 100 parts by weight of the total of the polymerizable monomer composition A, the volatile diluent B and the polymerization initiator C.

[0044] The present invention is further described in detail below based on examples, but is not intended to limit the present invention.

[0045] The abbreviations used in the present invention represent the following compounds:

[0046] THETA: tris(2-acryloyloxyethyl)isocyanurate;

[0047] DPPA: polydipentaerythritol pentaacrylate;

[0048] DPHA: polydipentaerythritol hexaacrylate;

[0049] DI-TMPT: di(trimethylolpropane)tetraacrylate;

[0050] UDMA: urethane dimethacrylate;

[0051] MDP: 10-methacryloyloxydecyl phosphate;

[0052] AUP: 11-acryloyloxyundecylphosphoric acid;

[0053] 4-MET: 4-methacryloyloxyethyl trimellitic acid;

[0054] K570: γ-methacryloxypropyltrimethoxysilane;

[0055] MMA: methyl methacrylate;

[0056] EtAA: ethyl acetate;

[0057] n-BuAA: butyl acetate;

[0058] EtOH: ethanol;

[0059] H2O: distilled water;

[0060] CQ: camphorquinone;

[0061] DMABEE: ethyl p-dimethylaminobenzoate;

[0062] DMABEH: 2-ethylhexyl dimethylaminobenzoate;

[0063] TPO: 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide;

[0064] MEHQ: hydroquinone monomethyl ether;

[0065] BHT: 2,6-di-tert-butylphenol.

[0066] Example 1

[0067] The surface modification material is prepared according to the composition ratio of Example 1 in Table 1. The multifunctional polymerizable monomer tri(2-acryloyloxyethyl)isocyanurate (abbreviation: THETA) used is a tri-polymerization functional group monomer (N=3), with a molecular weight of 423.38 and a density of 1.289 g / ml. It is white waxy at room temperature. The polymerized functional group density is calculated to be 9.2 mmol / ml according to the formula: monomer polymerized functional group density = N×D×1000 / M. Among them, the acidic group-containing monomer is 10-methacryloyloxydecyl phosphate (abbreviation: MDP); the volatile diluent is methyl methacrylate (abbreviation: MMA), and its saturated vapor pressure at 20 degrees is 3.9 KPa.

[0068] 1. Surface curing state of the surface modification material layer after light exposure

[0069] Drop the surface modification material composition into the mixing dish, use a small brush to dip the surface modification material composition and gently apply a layer on the sintered zirconia block. After leaving it for 15-20 seconds, use a dental light curing lamp to irradiate the coating for 20 seconds. Use a cotton swab to touch the coating surface after light irradiation, and observe whether the surface is shiny or has a sticky unpolymerized layer. Confirm that the surface is shiny and there is no unpolymerized layer.

[0070] 2. Bonding strength between surface modification material coating and ceramic surface

[0071] 1) Paste a 4 mm diameter hollow cellophane tape on the surface of the light-cured coating to limit the bonding area;

[0072] 2) At room temperature of 25±2°C, drop 0.18g of MMA, about 0.015g of butoxydibutyl boron, and then add 0.16g of polymethacrylic acid powder into a mixing dish, and mix gently for 10 seconds to make a resin mud;

[0073] 3) The resin mud was applied on the adhesive surface prepared in step 1), and an acrylic rod with a diameter of 6 mm and a length of 8 mm was placed and gently pressed down to adhere, thereby preparing a sample for adhesion test.

[0074] The sample for adhesion test was placed at room temperature for 30 minutes, and then immersed in distilled water at 37°C for 24 hours. The adhesion strength between the surface modification material coating and zirconium oxide was measured with reference to the test method of ISO / TS 11405-2015 (Dentistry - Tooth Structure Adhesion Test) (crosshead speed was 1.0 mm / min), and the average of the measured values ​​of 5 tests was taken. The adhesion strength was 8.1 MPa.

[0075] From the results of Example 1, it can be seen that the surface modification material composed of a multifunctional polymerizable monomer (first component a1) containing three polymerizable functional groups which has a polymerizable functional group density of 9.2 mmol / ml and is solid at room temperature, an appropriate amount of a polymerizable monomer containing an acidic group (second component a2), a volatile diluent B and a polymerization initiator C can obtain a polymerized cured film with good coating and bonding strength.

[0076] Example 2, 3

[0077] The difference between Examples 2 and 3 and Example 1 is that the content of the first component a1 is different. See Table 1 for specific ratios and results.

[0078] From the results of Examples 2 and 3 in Table 1, it can be seen that the surface modification material consisting of the first component a1 with a content between 20 parts by weight and 50 parts by weight, an appropriate amount of the second component a2, a volatile diluent B and a polymerization initiator C can obtain a polymerized cured film with good coating and bonding strength.

[0079] Embodiment 4,5

[0080] The difference between Examples 4 and 5 and Example 1 is that the content of the second component a2 is different. See Table 1 for specific ratios and results.

[0081] From the results of Examples 4 and 5 in Table 1, it can be seen that the surface modification material composed of 0.3 parts by weight or 3 parts by weight of the second component a2, an appropriate amount of the first component a1, a volatile diluent B and a polymerization initiator C can obtain a polymerized cured film with good coating and bonding strength.

[0082] Table 1. Examples 1-5

[0083]

[0084] Embodiment 6, 7

[0085] The difference between Examples 6 and 7 and Example 1 is that the content of polymerization initiator C is different. See Table 2 for specific ratios and results.

[0086] From the results of Examples 6 and 7 in Table 2, it can be seen that the surface modification material composed of 0.6 parts by weight or 5 parts by weight of polymerization initiator C, and appropriate amounts of first component a1, second component a2 and volatile diluent B can obtain a polymerized cured film with good coating and bonding strength.

[0087] Embodiment 8,9

[0088] The difference between Example 8 and Example 9 and Example 1 is that the first component a1 is different. See Table 2 for specific proportions and results.

[0089] The multifunctional polymerizable monomer containing three or more polymerizable functional groups used in Example 8 is polydipentaerythritol pentaacrylate (abbreviation: DPPA), a five-polymerizable functional group monomer (N=5), with a molecular weight of 524.51 and a density of 1.155 g / ml. It is a viscous liquid at room temperature (viscosity at 25 degrees is 5000-7400 cps). The polymerizable functional group density is calculated according to the above formula to be 11.0 mmol / ml.

[0090] The multifunctional polymerizable monomer containing three or more polymerizable functional groups used in Example 9 is polydipentaerythritol hexaacrylate (abbreviation: DPHA), a six polymerizable functional group monomer (N=6), with a molecular weight of 578.57 and a density of 1.19 g / ml. It is a viscous liquid at room temperature (viscosity of 4000-7000 cps at 25 degrees). The polymerizable functional group density calculated according to the above formula is 12.3 mmol / ml.

[0091] From the results of Examples 8 and 9 in Table 2, it can be seen that the surface modification material composed of a multifunctional polymerizable monomer containing three or more polymerizable functional groups with a polymerizable functional group density of 11.0 mmol / ml and 12.3 mmol / ml and a viscosity of 4000 cps or more at 25 degrees, as well as an appropriate amount of the second component a2, a volatile diluent B, and a polymerization initiator C can obtain a polymerized cured film with good coating and bonding strength.

[0092] Example 10

[0093] The difference between Example 10 and Example 1 is that the first component a1 uses a mixture of tris(2-acryloyloxyethyl)isocyanurate (abbreviation: THETA) and polydipentaerythritol hexaacrylate (abbreviation: DPHA). See Table 2 for specific ratios and results.

[0094] From the results of Example 10 in Table 2, it can be seen that a surface modification material consisting of a mixture of multifunctional polymerizable monomers containing three or more polymerizable functional groups, which has a polymerizable functional group density of more than 8.0 mmol / ml, is solid at room temperature and has a viscosity of more than 4000 cps at 25 degrees, and an appropriate amount of the second component a2, a volatile diluent B, and a polymerization initiator C can obtain a polymerized cured film with good coating and bonding strength.

[0095] Table 2. Examples 6-10

[0096]

[0097] Embodiments 11, 12, 13

[0098] The difference between Examples 11, 12 and 13 and Example 1 is that the second component a2 is different. See Table 3 for specific proportions and results.

[0099] Example 11 used 11-acryloyloxyundecyl phosphoric acid (abbreviation: AUP); Example 12 used 4-methacryloyloxyethyl trimellitic acid (abbreviation: 4-MET); Example 13 used a mixture of 10-methacryloyloxydecyl phosphate (abbreviation: MDP) and γ-methacryloyloxypropyltrimethoxysilane (abbreviation: K570).

[0100] From the results of Examples 11, 12, and 13 in Table 3, it can be seen that the surface modification material composed of different acidic group-containing monomers or a mixture of acidic group-containing monomers and polymerizable monomers containing alkoxysilane, as well as an appropriate amount of the first component a1 and a volatile diluent B and a polymerization initiator C can obtain a polymerized cured film with good coating and bonding strength.

[0101] Embodiment 14, 15

[0102] The difference between Examples 14 and 15 and Example 1 is that the volatile diluent B is different. See Table 3 for specific ratios and results.

[0103] The volatile diluent B used in Example 14 is ethyl acetate (abbreviation: EtAA), and its saturated vapor pressure at 20 degrees is 10.1 KPa; the volatile diluent B used in Example 15 is butyl acetate (abbreviation: n-BuAA), and its saturated vapor pressure at 20 degrees is 1.2 KPa.

[0104] From the results of Examples 14 and 15 in Table 3, it can be seen that the use of a volatile diluent B having a saturated vapor pressure of more than 1.0 KPa at 20 degrees, and a surface modification material composed of an appropriate amount of the first component a1 and a polymerization initiator C can obtain a polymerized cured film with good coating and bonding strength.

[0105] Table 3. Examples 11-15

[0106]

[0107] Embodiment 16, 17

[0108] The difference between Examples 16 and 17 and Example 1 is that the volatile diluent B is different. See Table 4 for specific ratios and results.

[0109] The volatile diluent B used in Examples 16 and 17 is ethanol (abbreviation: EtOH), and its saturated vapor pressure at 20 degrees is 5.8 KPa.

[0110] From the results of Examples 16 and 17 in Table 4, it can be seen that the use of a volatile diluent B having a saturated vapor pressure of more than 1.0 KPa at 20 degrees, and a surface modification material composed of an appropriate amount of the first component a1 and a polymerization initiator C can obtain a polymerized cured film with good coating and bonding strength.

[0111] Embodiment 18

[0112] The difference between Example 18 and Example 1 is that a small amount of distilled water (abbreviation: H2O) is added to the surface modification material. See Table 4 for specific ratios and results.

[0113] It can be seen from the results of Example 18 that adding a small amount of distilled water to the surface modification material does not affect the ability of the present invention to obtain a polymerized cured film with good coating and bonding strength.

[0114] Embodiment 19, 20

[0115] The difference between Examples 19 and 20 and Example 1 is that a polymerization inhibitor is used separately in the surface modification material. See Table 4 for specific ratios and results.

[0116] From the results of Examples 19 and 20 in Table 4, it can be seen that the use of inhibitors in the surface modification materials alone does not affect the ability of the present invention to obtain a polymerized cured film having good coating and bonding strength.

[0117] Table 4. Examples 16-20

[0118]

[0119] Comparative Examples 1, 2

[0120] The difference between Comparative Examples 1 and 2 and Example 1 is that the content of the first component a1 is different. See Table 5 for specific ratios and results.

[0121] From the results of Comparative Examples 1 and 2 in Table 5, it can be seen that when the content of the first component a1 is too low, it is easy to cause incomplete coating; when the content of the first component a1 is too high, it is easy to cause uneven coating.

[0122] Comparative Example 3

[0123] The difference between Comparative Example 3 and Example 1 is that the surface modification material does not contain the second component a2 with an acidic group. See Table 5 for specific ratios and results.

[0124] From the results of Comparative Example 3 in Table 5, it can be seen that the surface modification material does not contain the second component a2 with an acidic group, and the cured coating film cannot obtain the required bonding strength with the ceramic surface.

[0125] Comparative Examples 4 and 5

[0126] The difference between Comparative Examples 4 and 5 and Example 1 is that the first component a1 is different. See Table 5 for specific proportions and results.

[0127] The multifunctional polymerizable monomer containing three or more polymerizable functional groups used in Comparative Example 4 is di(trimethylolpropane)tetraacrylate (abbreviation: DI-TMPT), a four-polymerizable functional group monomer (N=4), with a molecular weight of 466.52 and a density of 1.11 g / ml. It is a viscous liquid at room temperature (viscosity of 800-1500 cps at 25 degrees). The polymerizable functional group density calculated according to the above formula is 9.5 mmol / ml.

[0128] The multifunctional polymerizable monomer used in Comparative Example 5 is UDMA: dimethacrylate urethane (abbreviation: UDMA), a dipolymerizable functional group monomer (N=2), with a molecular weight of 470.56 and a density of 1.11 g / ml. It is a viscous liquid at room temperature (viscosity at 25 degrees is 9000-13000 cps). The polymerizable functional group density is calculated as 4.7 mmol / ml according to the above formula.

[0129] From the results of Comparative Example 4 in Table 5, it can be seen that although the multifunctional polymerizable monomer containing more than three polymerizable functional groups has a polymerizable functional group density higher than 8 mmol / ml, due to the low viscosity, the coating film after evaporation of the volatile diluent cannot effectively prevent the penetration of oxygen, and a dense and bright coating film cannot be obtained after curing.

[0130] From the results of Comparative Example 5 in Table 5, it can be seen that although the multifunctional polymerizable monomer has a relatively high viscosity, the density of the polymerized functional groups is low, the density of the polymerized crosslinking is insufficient during photopolymerization, and a dense and bright coating film cannot be obtained after curing.

[0131] Table 5. Comparative Examples 1-5

[0132]

[0133] Comparative Example 6

[0134] The difference between Comparative Example 6 and Example 1 is that the composition used is a common multifunctional adhesive composition. See Table 6 for specific ratios and results.

[0135] From the results of Comparative Example 6 in Table 6, it can be seen that a dense and bright coating film cannot be obtained after the multifunctional adhesive is cured.

[0136] Table 6. Comparative Example 6

[0137]

[0138] The surface modification material of the present invention can simply and directly modify the surface of a dental ceramic restoration, and can modify and adjust the size of the dental ceramic restoration, especially the surface of a ceramic crown. It is easy to use and simple to operate, reduces the restoration cost, improves the restoration efficiency, and meets the needs of surface modification and size adjustment of dental ceramic restorations, especially crowns.

[0139] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.

Claims

1. A surface modification material for surface modification and size adjustment of dental ceramic restorations, characterized in that: include: A polymerizable monomer composition, comprising 20 to 50 parts by weight of a first component and 0.2 to 5 parts by weight of a second component, wherein the first component is a multi-functional polymerizable monomer having three or more polymerizable functional groups in the molecule, a polymerizable functional group density of the molecule greater than 8 mmol / ml, and being solid at room temperature or having a viscosity greater than 3000 cps at 25°C; and the second component is a polymerizable monomer selected from a group containing an acidic group or containing an acidic group and containing an alkoxysilane; Volatile diluents are organic solvents or polymerizable monomers having a vapor pressure greater than or equal to 1KPa and less than 10KPa at room temperature; and Photopolymerization initiator, the wavelength of photopolymerization is 365nm to 520nm; Wherein, the polymerizable functional group density of the monomers of the polymerizable monomer composition is: Monomer polymerization functional group density = N × D × 1000 / M; Wherein, the unit of monomer polymerizable functional group density is mmol / ml, N is the number of polymerizable functional groups in one molecule of monomer; D is the density of the polymerizable monomer, in g / ml; M is the molar mass of the polymerizable monomer, in g / mol.

2. The surface modification material according to claim 1, characterized in that The first component is tris(2-acryloyloxyethyl)isocyanurate, polydipentaerythritol pentaacrylate or polydipentaerythritol hexaacrylate.

3. The surface modification material according to claim 1, characterized in that: The acidic group of the second component is a carboxyl group, a carboxylic anhydride group and / or a phosphoric acid group.

4. The surface modification material according to claim 1, characterized in that: The polymerizable monomer of the second component is 4-methacryloyloxyethyl trimellitic acid, 10-methacryloyloxydecyl phosphate, di-10-methacryloyloxydecyl phosphate, 11-acryloyloxyundecyl phosphoric acid and / or di-11-acryloyloxyundecyl phosphoric acid.

5. The surface modification material according to claim 1, characterized in that: The organic solvent of the volatile diluent is ethanol or propyl acetate.

6. The surface modification material according to claim 1, characterized in that: The polymerizable monomer of the volatile diluent is methyl methacrylate or ethyl methacrylate.

7. The surface modification material according to claim 1, characterized in that: The photopolymerization initiator is an α-diketone compound, an alkyl phenone compound, an acyl phosphine oxide compound, a titanocene compound, an oxime ester compound, a benzoin compound, an acetophenone compound, a benzophenone compound, a thioxanthone compound, an α-acyl oxime ester compound, a benzoylformate compound, a benzil compound, an azo compound, a diphenyl sulfide compound, an organic pigment compound, an iron-phthalocyanine compound, a benzoin ether compound or an anthraquinone compound.

8. The surface modification material according to claim 1, characterized in that: It also includes a polymerization accelerator, which is an amine compound, a sulfinic acid compound, a barbituric acid compound, an aldehyde compound or a thiol compound, and the polymerization accelerator is 0.5 to 3 times the weight of the photopolymerization initiator.

9. The surface modification material according to claim 1, characterized in that: The present invention also includes a polymerization inhibitor, which is at least one of phenols such as hydroquinone, dibutylhydroquinone, hydroquinone monomethyl ether, 2,6-di-tert-butylphenol, 2,6-di-tert-butyl-p-cresol, catechol, pyrogallol, benzoquinone, 2-hydroxybenzoquinone, p-methoxyphenol, tert-butylcatechol, butylated hydroxyanisole, butylated hydroxytoluene, and tert-butylhydroquinone, and the added amount of the polymerization inhibitor is 50 to 20,000 ppm relative to the polymerizable monomer composition.

10. A dental ceramic restoration, characterized in that: The surface modification material according to any one of claims 1 to 9 is applied to form a coating to perform surface modification and size adjustment.